The People's Lawyer : The Center for Constitutional Rights and the Fight for Social Justice, From Civil Rights to Guantánamo - Ruben, Albert (Book collections on Project MUSE., 2011)
"There is hardly a struggle aimed at upholding and extending the rights embedded in the U.S. Constitution in which the Center for Constitutional Rights has not played a central role. Whether defending the rights of black people in the South, opponents of the war in Vietnam, and victims of torture worldwide, or fighting illegal actions of the U.S. government, the CCR has stood ready to take on all comers, regardless of their power and wealth. When the United States declared that the Constitution did not apply to detainees at Guantanamo, the CCR waded fearlessly into battle, its Legal Director declaring that "My job is to defend the Constitution from its enemies. Its main enemies right now are the Justice Department and the White House." In this first-ever comprehensive history of one of the most important legal organizations in the United States, the Center for Constitutional Rights, Ruben shows us exactly what it means to defend the Constitution. He examines the innovative tactics of the CCR, the ways in which a radical organization is built and nurtured, and the impact that the CCR has had on our very conception of the law. This book is a must-read for not only for lawyers, but for all the rest of us who may one day find our rights in jeopardy"--Provided by publisher